The Relationship Between Gadget Usage and Adolescents Eye Health - Kadek Sri Ariyanti; Made Dewi Sariyani; I Putu Eka Viqtrayana; Rini Winangsih (Nursing and Health Sciences Journal (NHSJ), 2022)
The changes in public life style cause the raising demand in practical communication media. The data from a survey conducted in 2014 in United States shows that the gadgets ownership in group of people ranged from 13 to 15 years old has increased from 35% to 55%, and tablet ownership has increased twice as much, from 18% to 37%. Referring to the previous study, it is said that teenagers are susceptible to experience the negative effect from the excessive use of gadget, for the gadget screen exposure could induce the release of dopamine hormone which has important role in shaping addictive trait. To prevent such impact, the government of Denpasar City should be having the latest data about the gadget use in teenagers, especially early teenagers. The study aims to determine the relationship between the use of gadgets with eye health in adolescent. Methods: This research uses quantitative methods. The research is conducted in SMP Negeri 3, 6, 7, 8 and 9 Denpasar. The data gathering was conducted from July 23 until August 19, 2020. The technique for determining the minimum sample size is the estimation of the proportion in a simple random sample with absolute precision. Results: Bivariate analysis with chi-square test showed p-value = 0.000. There is a relationship between gadget use and the eye health on teenager informants. Conclusion: There is a positive and significant relationship between the use of gadgets with eye health in adolescent.